Characteristics of adult patients with febrile neutropenia in a university hospital (Medellin, 2012-2016). - Arroyave Peña, Tatiana; Puerta Rojas, José David; Beltrán Benavidez, Rafael Eduardo; Salgado Gómez, Tania Margarita; Ramírez Cadavid, Diana Carolina; Arroyave Ávila, David; Ruiz Ceballos, Ana Camila; Londoño Aguilar, Luisa Fernanda; Jaimes Barragán, Fabián Alberto (Medicina UPB, 2019)
Objective: Febrile neutropenia is a condition present in patients with some degree of immunosuppression associated to oncology treatment, which leads to risks of infectious complications and death. The aim of this research is to describe the clinical, microbiological and prognostic characteristics in patients with febrile neutropenia in a university hospital. Methodology: Retrospective cohort study developed between January of 2012 and June of 2016 in patients with febrile neutropenia (neutrophils 38.3 °C), who were hospitalized in the Pablo Tobon Uribe Hospital of Medellin, Colombia. Results: 226 patients were evaluated, 96% of who had an oncological diagnostic. The main infectious sources were the skin and the gastrointestinal tract. Blood cultures were positive in 31%. The main pathogen was Escherichia coli in 26% and the overall hospital mortality rate was 17%. Conclusions: The clinical characteristics of our population were similar to the national and international reports, but we found epidemiological differences in microbiological agents, bacterial resistance and mortality. Only one third of the patients presented bacteremia. E. coli remains the main pathogen involved.